The development of the status of Druze women in the 21st century - Faraj Falah, Janan (Frontiers in Sociology, 2023)
This article analyzes the social personal and religious reasons for the changing of the status of the Druze in Israel. In the 1970s, the first wave of teachers of the Druze females was after the opening of a special class only for Druze girls .in the last twenty years, there has been a fundamental change in the status of women. Following the general change in the status of women in Israeli society. This change led to an increase in the percentage of female Druze students compared to male Druze students. According to the Central Israeli Bureau of Statistics, in 2020,68.35 OF ALL Druze students for bachelor's degrees and 64.8% of those pursuing a master's degree were females. In addition, this in turn affected 6the various professions in which the Druze woman worked. This article will also discuss the effect of changing the status of the Druze society in general.